A proposal of structure and control overcoming conducted electromagnetic interference in a buck converter - Zakaria M’barki; Kaoutar Senhaji Rhazi; Youssef Mejdoub (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper describes modelling a step-down chopper designed for a photovoltaic application to study its performance of electromagnetic compatibility (EMC) in conducted mode. The EMC measurements attended at this stage have shown that the buck converter is a harmful device for its electromagnetic environment. Indeed, the fast-switching operation leads to higher levels of conducted and radiated electromagnetic interference (EMI) and subsequently facilitates the electromagnetic coupling with the surrounding environment. In this sense, we present a new proposal of structure and control based on a combination of two techniques, namely pseudo-random modulation and soft switching, thus minimizing the conducted electromagnetic emissions at the source. The usefulness of this new strategy, evaluated through a comparative study, lies in its efficiency compared to the classical PWM method, allowing both to reduce the rise of current and voltage gradients and spread the electromagnetic spectrum over a wide frequency range. The simulation results prove that a significant gain in EMC has been reached.